Successful treatment with placenta‐derived decidual stromal cells in a pediatric patient with life‐threatening acute gastrointestinal graft‐versus‐host disease. (13th June 2017) - Gustafsson, Britt; Frisk, Per; Szakos, Attilla; Sadeghi, Behnam; Ringdén, Olle; Frost, Britt‐Marie
Abstract: Severe aGvHD is a life‐threatening complication after allogeneic HSCT. The GI tract is considered to play a key role in aGvHD, where the disease process can start and is one of the major target organs. Here, we present a case of a one‐year‐old child with a life‐threatening GI‐aGvHD stage IV, post‐HSCT, resistant to steroids and MMF for 4 weeks. He was successfully treated with placenta‐derived DSC.